Clear Aligner Treatment: Indications, Advantages, and Adverse Effects—A Systematic Review - Clara Rasborg Hartogsohn; Liselotte Sonnesen (Dentistry Journal)
Background/Objectives: Clear aligner treatment (CAT) has gained interest among clinicians as well as among patients. The aim of the present study was to systematically review the literature regarding current viewpoints on indications, contraindications, advantages, disadvantages, and adverse effects in CAT. Methods: A search was performed in the PubMed and Embase databases, yielding 18 studies eligible for inclusion. Results: Current indications for CAT are mild to moderate malocclusions. Severe malocclusions with impactions or severe craniofacial skeletal deviations are contraindications. The advantages were oral hygiene and oral health as the most common, and disadvantages of CAT have been noted by several studies, including CAT still being inferior to fixed appliance treatment (FAT) in all orthodontic movements. Adverse effects were potential health risks due to microplastics and a decrease in condyle bone volume. Conclusions: No firm conclusions can be drawn regarding indications for CAT except for mild to moderate malocclusion. Severe malocclusions with impactions or severe craniofacial skeletal deviations are considered contraindications. In more complex cases, CAT is still considered inferior to FAT, although CAT contains advantages. There are disadvantages in CAT which clinicians should consider when choosing a type of orthodontic appliance for treating specific malocclusions. Only a few adverse effects in CAT were presented by the included studies. More high-quality research is needed regarding indications and contraindications for CAT.